The impact of prepreg aging on its processability and the postcure mechanical properties of epoxy-based carbon-fiber reinforced plastics. (February 2017) - Blass, D; Kreling, S; Dilger, K
Due to the intention to increase the product efficiency by weight reduction, the application of carbon fiber reinforced plastics and its processing becomes more and more important for the industrial production planning. The aviation industry mostly uses epoxy-based preimpregnated laminates (prepregs). These prepregs are stored in the refrigerated state and may be processed after defrosting only for a specific shelf-life or so-called out-time. This limitation in processing time reduces the efficiency of the entire production, for example due to the waste of material during production stops. To improve the production effectiveness the shelf-life should be as high as possible, to be able to avoid material waste during production stops. Therefore, the processability and the postcure mechanical properties of two representative prepregs were investigated during this study for different aging stages and correlated with the reactivity of the prepregs.